Realizing high thermoelectric performance in eco-friendly SnTe via synergistic resonance levels, band convergence and endotaxial nanostructuring with Cu2Te. (July 2020) - Hussain, Tanveer; Li, Xiaotong; Danish, Mazhar Hussain; Rehman, Mutee Ur; Zhang, Jian; Li, Di; Chen, Guang; Tang, Guodong
Abstract: SnTe is emerging as environment-friendly alternative to conventional thermoelectric material PbTe which contains toxic element. Here, we achieved an ultrahigh power factor and high thermoelectric performance of SnTe via the synergy of resonance levels, band convergence and endotaxial nanostructuring. We found that the coexistence of resonant levels (by In dopant) and band convergence (by Ca dopant) produce remarkable enhancement of Seebeck coefficient and ultrahigh power factor. The largest power factor reaches as high as ~42.2 μWcm −1 K −2 . Endotaxial Cu2 Te nanostructures were further introduced by a phase separation strategy, which plays a dominant role in reducing the lattice thermal conductivity. Meanwhile, it is revealed that Ca and In codoping enlarges band gap, therefore suppressing bipolar thermal conductivity. These electronic and thermal effects contribute to a record high ZT of ~1.85 at 823 K and a high average ZT of 0.67. This high performance material is low-cost, earth-abundant and environmentally-friendly, which are essential for the widespread use of thermoelectric modules. Graphical abstract: Image 1 Highlights: We reported a record ZT of 1.85 in SnTe via synergistic resonance levels, band convergence and endotaxial nanostructuring. High average ZT of 0.67 and thermoelectric efficiency η of 11.4% are achieved, which is larger than most of SnTe systems. Coexistence of resonant levels and band convergence produce large Seebeck coefficient and high power factor (42.2 μWcm −1 K −2 ). The high performance SnTe thermoelectrics was achieved by low cost and nontoxic elements doping.